2016
DOI: 10.1074/jbc.m115.674564
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of the HIV-1 Intron Splicing Silencer and Its Interactions with the UP1 Domain of Heterogeneous Nuclear Ribonucleoprotein (hnRNP) A1

Abstract: Splicing patterns in human immunodeficiency virus type 1 (HIV-1) are maintained through cis regulatory elements that recruit antagonistic host RNA-binding proteins. The activity of the 3 acceptor site A7 is tightly regulated through a complex network of an intronic splicing silencer (ISS), a bipartite exonic splicing silencer (ESS3a/b), and an exonic splicing enhancer (ESE3). Because HIV-1 splicing depends on protein-RNA interactions, it is important to know the tertiary structures surrounding the splice sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 49 publications
(64 reference statements)
0
35
0
1
Order By: Relevance
“…An initial pool of 1024 structures was generated using Xplor-NIH 2.34[62] as previously described[63]. During this stage, hydrogen-bond, NOE, dihedral and planarity restraints were used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An initial pool of 1024 structures was generated using Xplor-NIH 2.34[62] as previously described[63]. During this stage, hydrogen-bond, NOE, dihedral and planarity restraints were used.…”
Section: Methodsmentioning
confidence: 99%
“…NMR restraints (RDC, NOE, hydrogen bond, sugar pucker and chirality) and simulation parameters were identical to those used for the production run of the previous step, with the exception that the temperature was held at 0K for 100 ps. Inclusion of the SAXS data was accomplished by utilizing the SAXS ab initio model (creation of which is described in SAXS materials and methods section) and the emap function[72], incorporated in a manner as previously described[63]. First, Supcomb[73] was used to align the SAXS molecular envelope to each structure while allowing the search for enantiomers.…”
Section: Methodsmentioning
confidence: 99%
“…Although NMR spectroscopy has historically been used to determine structures of relatively small RNAs that typically comprise fewer than 60 nucleotides [67,68,69,70,71,72,73,74,75], the above studies have shown that structures can be probed by NMR spectroscopy in RNAs comprising up to 688 nucleotides. When used in combination with cryo-electron microscopy (cryoEM) or small-angle X-ray scattering (SAXS), 3D structural information can be obtained for relatively large protein:RNA complexes [68,69].…”
Section: Discussionmentioning
confidence: 99%
“…When used in combination with cryo-electron microscopy (cryoEM) or small-angle X-ray scattering (SAXS), 3D structural information can be obtained for relatively large protein:RNA complexes [68,69]. An advantage of the Adenosine-H2 detected, 2 H-edited method described above is that it enables direct detection of structure, even in RNAs that exist as equilibrium mixtures of species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation